Effects of bevelled nozzles on standoff shocks in supersonic impinging jets - Lim, H.D. (2021)
Moderately under-expanded jets issuing from a circular baseline and two bevelled circular nozzles impinging upon a perpendicular flat plate were experimentally studied. The effects of nozzle-pressure-ratio and separation distance variations on the standoff shock formations were investigated with schlieren visualizations and a visual hull based three-dimensional (3D) shock reconstruction technique to provide deeper insights into their 3D features. Across all flow configurations arising from the different combinations of these parameters, results indicated that the bevelled nozzles are effective in introducing asymmetry to the standoff shock geometries. Depending on the exact flow configuration, standoff shock locations may also undergo significant upstream displacements. In particular, the single-bevelled nozzle produces highly unsteady standoff shocks with asymmetric oscillation amplitudes along both side of the nozzle lip regions. Changes to the standoff shock key characteristics were observed to be sensitive towards the jet shock structures and reflection point modified by the bevelled nozzle exits. In particular, the strength and relative position of the reflection point are identified as the major contributing factors influencing the upstream static pressure distribution of the standoff shock, hence leading to the observed changes in the standoff shock behaviour.